Pump selection at his work on the network with variable resistance over time - Хованський, Сергій Олександрович; Неня, Віктор Григорович (Eastern-European Journal of Enterprise Technologies, 2010)
Proposed use of ordered diagrams of water consumption for the analysis of modes of pumping equipment. A method of determining the optimal parameters of the pump operating in the hydraulic network with baser resistance over time, according to the criterion of minimum energy consumption and determine the impact of external factors of the system.